The Gait of Islamic Unions in the Political Stage of the National Movement - *Yusuf Perdana; Sumargono Sumargono; Rinaldo Adi Pratama; Nur Indah Lestari (Universitas Syiah Kuala, 2022)
The purpose of this study was to describe the political activities of an Islamic organization, namely Sarekat Islam in 1916-1921. The Union of Islamic Organizations (SI) started from the Sarekat Dagang Islam (SDI) which was transformed into the Sarekat Islam with the aim of expanding its reach which was not only limited to traders. SI turned into an association that encouraged the socio-political struggle of the people at the beginning of the twentieth century. The method used in this study is the Historical Method, namely heuristic steps, source criticism, data interpretation and historiography. The results of the study are the political progress of the Islamic organization, namely Sarekat Islam in 1916-1921 through national congresses in several regions by bringing up socio-political problems, which culminated in 1921 with the split of Sarekat Islam itself with two streams, namely Sarekat Islam Merah with socialist principles - communists led by Semaun and Sarekat Islam Putih based on nationality and religion led by Tjokroaminoto.